The mediating role of anxiety and depression in the relationship between alexithymia, somatosensory amplification, and functional impairment in fibromyalgia - Arda Kazim Demirkan; Gizem Gerdan (Frontiers in Psychiatry, 2025)
ObjectiveFibromyalgia Syndrome (FMS) is a chronic multifaceted condition characterized by widespread musculoskeletal pain, fatigue, cognitive difficulties, and emotional distress, predominantly affecting women. Although psychological factors are frequently implicated, their interrelations remain unclear. Key variables include alexithymia (particularly the difficulty identifying feelings [DIF] subdimension), somatosensory amplification (SSA), and mood symptoms. This study aimed to examine differences in alexithymia, anxiety, depression, and SSA between individuals with FMS and healthy controls, and explore how these variables relate within the FMS group.MethodsThe study included 283 women (mean age = 31.84, SD = 4.02), comprising 142 FMS patients (mean age = 32.20, SD = 4.41) and 141 healthy controls (mean age = 31.48, SD = 3.58). Participants completed self-report measures assessing alexithymia, anxiety, depression, SSA, and functional impairment. Statistical analyses included independent samples t-tests and multivariate analyses of covariance (MANCOVA) to compare groups, and mediation analyses to examine indirect effects of anxiety and depression.ResultsThe FMS group reported significantly higher levels of anxiety, depression, DIF, and SSA compared to controls. However, after controlling for anxiety and depression, DIF differences were attenuated and SSA differences were no longer statistically significant. Within the FMS group, individuals with high alexithymic traits also exhibited higher SSA and mood symptoms; however, SSA elevations were no longer evident after accounting for anxiety and depression. Mediation analyses revealed that anxiety and depression significantly mediated the relationship between (a) DIF and functional impairment, and (b) SSA and functional impairment.ConclusionFindings underscore the importance of emotional dysregulation and somatic sensitivity in FMS. Anxiety and depression appear to be key pathways linking these psychological traits to functional outcomes. Interventions aimed at improving emotional awareness and regulation may alleviate mood symptoms and enhance daily functioning in individuals with FMS.